Persistent Pulmonary Hypertension of the Newborn: Pathophysiological Mechanisms and Novel Therapeutic Approaches - Martinho, Sofia; Adão, Rui; Leite-Moreira, Adelino F.; Brás-Silva, Carmen (Frontiers in Pediatrics, 2020)
Persistent pulmonary hypertension of the newborn (PPHN) is one of the main causes of neonatal morbidity and mortality. It is characterized by sustained elevation of pulmonary vascular resistance (PVR), preventing an increase in pulmonary blood flow after birth. The affected neonates fail to establish blood oxygenation, precipitating severe respiratory distress, hypoxemia and eventually death. Inhaled nitric oxide (iNO), the only approved pulmonary vasodilator for PPHN, constitutes, alongside supportive therapy, the basis of its treatment. However, nearly 40% of infants are iNO-resistant. The cornerstones of increased PVR in PPHN are pulmonary vasoconstriction and vascular remodeling. A better understanding of PPHN pathophysiology may enlighten targeted and more effective therapies. Sildenafil, prostaglandins, milrinone and bosentan, acting as vasodilators, besides glucocorticoids, playing a role on reducing inflammation, have all shown potential beneficial effects on newborns with PPHN. Furthermore, experimental evidence in PPHN animal models supports prospective use of emergent therapies, such as sGC activators/stimulators, L-citrulline, Rho-kinase inhibitors, PPAR-γ agonists, rhSOD, BH4 analogues, ω-3 LC-PUFAs, 5-HT2A receptor antagonists and rhVEGF. This review focuses on current knowledge on alternative and novel pathways involved in PPHN pathogenesis, as well as recent progress regarding experimental and clinical evidence on potential therapeutic approaches for PPHN.